De la projimidad a la hospitalidad : hacia el rostro desnudo de la íntima vulnerabilidad - Campana, Silvia Julia (Sapientia, 2019)
The parable of the Good Samaritan moves deeply because it questions our lives before the question "Which of the three do you think behaved as a neighbor of the man assaulted by the thieves?" Pedro Laín Entralgo begins his work Teoría y Realidad del otro from this evangelical text trying to show the levels of the encounter. Projimity is the last category, the highest, marked by the love that spills for free and the belief in the need of the other. We believe, from the reading of Levinas, that hospitality manifests a reality that emerges from the previous one but takes care of the reciprocal weakness of the one who is hosted and the one who hosts. The vulnerability shows the limit and the challenge that each hospital encounter offers, linked to the true intimacy that only manifests itself in the binding encounter (François Julien).